(untitled) (Bulletin KNOB, 2007)
The first study, which touched upon the phenomenon of commercial gothic in the Netherlands, was carried out twenty years ago by the Dutch architectural historian Ruud Meischke. Meischke proposed that in the fifteenth century, as a consequence of high transportation costs and tolls, stones for building were increasingly cut into shape in the quarries in the southern Netherlands rather than at the building site. At the end of the century major parts of churches were delivered as a kind of ’prefab’ that could be assembled on the spot. Since Meischke published his challenging thesis about prefabrication and export architecture, it has attracted the attention of an international scholarly audience. However, it still lacks a profound basis and until now it was not known in which ways the changes in the ’late gothic’ building practice influenced architectural design. By comparing details of many churches in the Netherlands, my paper will elaborate on the ways in which prefabrication in the quarries of Brabant generated the spread of specific architectural strategies and architectural forms. I will argue that the physical separation of cutting and assembling implied several technical limitations which, amongst other factors, can explain the preference for columns instead of compound piers in Holland. In particular, the constructional imperfections indicate that this construction system depending on the column provided the flexibility required for the assemblage of export architecture. Furthermore, I will suggest that the increasing importance of commercial stone trade was significant for the standardisation of an architectural repertoire. I made detailed studies of the mouldings of the most important churches in the Low Countries. By connecting the results of this ’categorised analysis’ to archival material, it has been possible to discern products developed by the masons workshops at the quarries. In analysing commercial gothic, my research shows that the development of architectural design and changes in the building industry went hand in hand from their earliest beginnings.